Anthropogenic fine aerosols dominate the wintertime regime over the northern Indian Ocean. Issue 1 (1st January 2018) - Budhavant, Krishnakant; Bikkina, Srinivas; Andersson, August; Asmi, Eija; Backman, John; Kesti, Jutta; Zahid, H.; Satheesh, S. K.; Gustafsson, Örjan
Abstract: This study presents and evaluates the most comprehensive set to date of chemical, physical and optical properties of aerosols in the outflow from South Asia covering a full winter (Nov. 2014 – March 2015), here intercepted at the Indian Ocean receptor site of the Maldives Climate Observatory in Hanimaadhoo (MCOH). Cluster analysis of air-mass back trajectories for MCOH, combined with AOD and meteorological data, demonstrate that the wintertime northern Indian Ocean is strongly influenced by aerosols transported from source regions with three major wind regimes, originating from the Indo-Gangetic Plain (IGP), the Bay of Bengal (BoB) and the Arabian Sea (AS). As much as 97 ± 3% of elemental carbon (EC) in the PM10 was also found in the fine mode (PM2.5 ). Other mainly anthropogenic constituents such as organic carbon (OC), non-sea-salt (nss) -K +, nss-SO4 2− and NH4 + were also predominantly in the fine mode (70–95%), particularly in the air masses from IGP. The combination at this large-footprint receptor observatory of consistently low OC/EC ratio (2.0 ± 0.5), strong linear relationships between EC and OC as well as between nss-K + and both OC and EC, suggest a predominance of primary sources, with a large biomass burning contribution. The particle number-size distributions for the air masses from IGP and BoB exhibited clear bimodal shapes within the fine fraction with distinct accumulation (0.1 μm < d < 1 μm) and Aitken (0.025 μm < d < 0.10 μm) modes. This study also supports that IGP is a key source region for the wider South Asia and nearby oceans, as defined by the criteria that anthropogenic AODs exceed 0.3 and absorption AOD > 0.03. Taken together, the aerosol pollution over the northern Indian Ocean in the dry season is dominated by a well-mixed long-range transported regime of the fine-mode aerosols largely from primary combustion origin.